Ultrasound-assisted butyl acetate synthesis catalyzed by Novozym 435: Enhanced activity and operational stability - Martins, Andrea B.; Schein, Mirela F.; Friedrich, John L. R.; Fernández-Lafuente, Roberto; Ayub, Marco A. Z.; Rodrigues, Rafael C. (Ultrasonics Sonochemistry, 2013)
The influence of low-frequency ultrasound (40 kHz) in the esterification reaction between acetic acid and butanol for flavor ester synthesis catalyzed by the commercial immobilized lipase B from Candida antarctica (Novozym 435) was evaluated. A central composite design and the response surface methodology were used to analyze the effects of the reaction parameters (temperature, substrate molar ratio, enzyme content and added water) and their response (yields of conversion in 2.5 h of reaction). The reaction was carried out using n-hexane as solvent. The optimal conditions for ultrasound-assisted butyl acetate synthesis were found to be: temperature of 46 °C; substrate molar ratio of 3.6:1 butanol:acetic acid; enzyme content of 7%; added water of 0.25%, conditions that are slightly different from those found using mechanical mixing. Over 94% of conversion was obtained in 2.5 h under these conditions. The optimal acid concentration for the reaction was determined to be 2.0 M, compared to 0.3 M without ultrasound treatment. Enzyme productivity was significantly improved to around 7.5-fold for each batch when comparing ultrasound and standard mechanical agitation. The biocatalyst could be directly reused for 14 reactions cycles keeping around 70% of its original activity, while activity was virtually zeroed in the third cycle using the standard mixing system. Thus, compared to the traditional mechanical agitation, ultrasound technology not only improves the process productivity, but also enhances enzyme recycling and stability in the presence of acetic acid, being a powerful tool to improve biocatalyst performance in this type of reaction. This work was supported by grants from Fundação de Amparo a Pesquisa do Rio Grande do Sul (FAPERGS – ARD/2011), from CNPq (Brazilian Bureau of Science and Technology), and CTQ2009-07568 from Spanish Ministerio de Ciencia e Innovación. Peer Reviewed